PROGRESIVITAS ILMU PENGETAHUAN DAN TEKNOLOGI DALAM PENGEMBANGAN KARAKTER PADA PESERTA DIDIK - Alfian Erwinsyah; Said Subhan Posangi; Putriani L. Maliki; Muhammad Arif Ferdiansyah (LP2M IAIN Sultan Amai Gorontalo, 2024)
This research aims to analyze research articles on the progressivity of the application of science and technology to the development of students' character This research is a literature study using the Narrative Literature Review method. Data sources come from reputable international journals contained in the Scopus database, accessed through scopus.com, using keywords that have been determined from the initial study, namely Science and Technology and character. The research period covered the last 4 years (2019-2023) and the scope in the country of Indonesia, where 4 articles were obtained that fit the research objectives. From the analysis of the journal articles, some important information was found, including the author's contribution, diagnostic methods used, and content relevant to the research topic on the relationship between Science and Technology and character. The results found are (1) Using ICT-based Learning Media in introducing and teaching about the character of environmental care to students (2) Using LCD media and learning resources from the internet for problem solving of moral and social situations represented visually in the form of animated sketches. (3) Using a digital technology-based evaluation system Automated Short Essay Scoring directly affects students' confidence and character (4) Implementing a 15-minute reading system using ICT by browsing learning websites before learning can increase confidence to learn.